Atividade da microbiota do solo e desenvolvimento de mudas de bananeira biofertirrigadas. - Saraiva, João Paulo Bezerra (2009)
Brazil is a major producer of banana (Musa sp.), Accounting for 10% of the total world production (FAO, 2002). From this perspective, we see the need to increase their production, and among the strategies adopted, one can anticipate the acclimatization phase, through the association of banana seedlings with mycorrhizal fungi. Biofertilizers commonly refer to the effluent resulting from aerobic or anaerobic fermentation of organic products alone or supplemented with mineral products. They are used in agriculture for various purposes, and its application promotes the improvement of physical and chemical properties and stimulating biological activity. The objective of this study was to evaluate the development of banana plants subjected to biofertilizer irrigation applied at different stages of their development and activity of the microbiota of a Cambisol Latossólico Eutrophic. The experiment was conducted in a greenhouse belonging to the sector of Soil Microbiology, Department of Soil Science, Federal University of Ceará (UFC). The soil used in the experiment was collected in an area of native vegetation, located in the area of commercial cultivation of banana, belonging to the Frutacor Tableland Farm, located in the city of Quixeré, Ceará. Was considered, for purposes of collection, the soil to a depth of 0 to 20 cm. Initially, the samples were sent to the Laboratory of Soil Microbiology, Department of Soil Science, where it recognized soil preliminary analysis for extraction and quantification of species of mycorrhizal fungi occurring naturally in the soil. The analysis consisted of extraction of spores, using the technique of wet sieving (Gerdemann & Nicolson, 1963). The experiment consisted of 12 treatments with 09 replicates, and 01 control treatment with 15 repetitions, totaling 123 plots. After 30, 45 and 60 days after planting (DAP, were removed 03 repetitions of the treatments, respectively, for evaluation of the mycorrhizal root. In the interval between the stages of planting seedlings and early application of biofertilizer was applied nutrient solution Hewitt (1966) no phosphorus for all the samples and the control treatment (T13) were given a complete nutrient solution with phosphorus, weekly until 90 days after acclimatization (Phase 1). Phase 2, after application of the treatments mentioned above, the evaluation consisted of the following: growth, content of mineral nutrients in plant root colonization (technical Phillips & Hayman, 1970 and Giovanetti & Mosse, 1980), determination of soil microbial biomass (MBC) according to Vance et al. (1987), soil basal respiration (SBR), quantification of CO2 released in mg C-CO2/100 cm3 of soil, during the time interval used in monitoring, and metabolic quotient (qCO2) calculated by the ratio of respiration basal and microbial biomass-C (Anderson & Domsch, 1978). The experiment was carried out using a randomized block design in a factorial 3 x 4. The soilsand mixture biofertilizer received in three different times of application (30,45 and 60 days after planting the seedlings), in four doses (0, 25, 50, 100%). The data were submitted to analysis of variance by F test and compare the means by Duncan test at 5% probability. After evaluating the results, we concluded that the biofertilization banana may occur 30 days after planting, and the 100% concentration the most suitable for plant growth; The biofertilizer at 100% independent the period that is initiated, promoted the production of dry matter and the contents of macronutrients (N, P, K, S, Ca, Na and Mg). The microbiological parameters were not influenced by the doses or times of application of biofertilizer, except for the metabolic quotient (qCO2) which was lower when applied to 100% dose of biofertilizer.